The limits of self-governance when cooperators get punished: Experimental evidence from urban and rural Russia - Simon Gächter; Benedikt Herrmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
We report evidence from public goods experiments with and without punishment which we onducted in Russia with 566 urban and rural participants of young and mature age cohorts. Russia is interesting for studying voluntary cooperation because of its long history of collectivism, and a huge urban-rural gap. In contrast to previous experiments we find no cooperation-enhancing effect of punishment. An important reason is that there is punishment of contributors in all four subject pools. Thus, punishment can also undermine the scope for self-governance in the sense of high levels of voluntary cooperation that are sustained by sanctioning free riders only.
Keywords: H41; C91; D23; C72; 330; social norms; free riding; misdirected punishment; experiments; Verhaltensökonomik; Kooperation; Soziale Norm; Trittbrettfahrerverhalten; Test; Russland